What does Research mean? (2010)
Interview with Ana María Peralta, participant of Expeditions to Knowledge, especifically Expedition to History: “At EAFIT Children's University we use research as a way of getting closer to knowledge, but this concept of research grows and evolves in the different stages that we live. I understood that research is not just searching, it is loving what you do, asking questions, understanding concepts and putting all the necessary means to achieve knowledge. "